SPROUTING SUSTAINABLE INDUSTRIAL AND TECHNOLOGICAL WORKFORCE THROUGH TECHNICAL VOCATIONAL EDUCATION AND TRAINING IN SOUTH-SOUTH, NIGERIA - Jane Itohan Oviawe; Pauline E. Ehirheme (Journal of Vocational Education Studies, 2020)
The call for continuous creation of industrial and technological workforce cannot be overlooked, in view of the fact that it will boost the sustainable industrial and technological development of any nation. A vital programme that can bring into being requisite workforce for sustainable industrial and technological development is Technical Vocational Education and Training (TVET). To this end, this study investigated the strategies for sprouting sustainable industrial and technological workforce through TVET in Nigeria using the descriptive survey research design. The study was guided with two research questions and two hypotheses. The sample was made up of 300 respondents comprising of 154 TVET Lecturers from Universities and 146 TVET industry-based workers in South-South Geopolitical Zone of Nigeria, who were selected using simple random and convenience sampling techniques respectively. The instrument used for data collection was a 69-item questionnaire which was validated by three experts. The reliability of the instrument was determined using Cronbach Alpha and a reliability coefficient of .86 was obtained. Mean and standard deviations statistics were used to answer the research questions, whereas t-test statistic was used to test the null hypotheses at .05 level of significance. The findings of this study revealed that TVET programmes had some policy-related challenges; and TVET institutions-workplace collaboration is a possible strategy for sprouting sustainable industrial and technological workforce in Nigeria. Thus, among others, it was recommended that firm TVET policy document be set-up by government and all stakeholders to appropriately synchronize TVET programmes towards sprouting sustainable industrial and technological workforce in Nigeria.